2017
DOI: 10.5812/iranjradiol.40723
|View full text |Cite
|
Sign up to set email alerts
|

Are Bismuth Shields Useful in Dentomaxillofacial Radiology Practice for the Protection of Eyes and Thyroid Glands from Ionizing Radiation?

Abstract: Background: The eye lens and thyroid gland are sensitive to radiation and have a risk of being exposed to primary beams and scattered radiation during dental radiographic examinations. Objectives: The present study was aimed to evaluate the effectiveness of bismuth shielding in decreasing eye lens and thyroid radiation dose in periapical radiography (PR), orthopantomography (OPTG), and cone beam computed tomography (CBCT) examinations. There is no information in relevant literature regarding the use of bismuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
2
0
4
Order By: Relevance
“…Teknik CBCT memerlukan dosis efektif lebih besar dibandingkan dengan teknik radiografi dua dimensi (2-D) pada umumnya, yaitu lebih dari 100 µSv. 2,26,27 Risiko efek paparan radiasi dipengaruhi oleh parameter pada mesin CBCT. 28 Field of View (FOV) merupakan salah satu parameter yang berdampak paling besar terhadap dosis radiasi pemeriksaan CBCT karena ukuran FOV menunjukkan luas area yang terpapar oleh radiasi primer.…”
Section: Fungsi Pelindung Tiroid Pada Teknik Radiografi Sefalometri Dunclassified
See 1 more Smart Citation
“…Teknik CBCT memerlukan dosis efektif lebih besar dibandingkan dengan teknik radiografi dua dimensi (2-D) pada umumnya, yaitu lebih dari 100 µSv. 2,26,27 Risiko efek paparan radiasi dipengaruhi oleh parameter pada mesin CBCT. 28 Field of View (FOV) merupakan salah satu parameter yang berdampak paling besar terhadap dosis radiasi pemeriksaan CBCT karena ukuran FOV menunjukkan luas area yang terpapar oleh radiasi primer.…”
Section: Fungsi Pelindung Tiroid Pada Teknik Radiografi Sefalometri Dunclassified
“…Pengurangan ukuran FOV untuk membatasi paparan radiasi primer hanya pada area yang perlu diamati sangat perlu diterapkan karena dapat mereduksi dosis efektif tanpa mengurangi kualitas citra CBCT. 26,30 Reduksi dosis efektif oleh pelindung tiroid akan lebih efektif jika FOV tidak berukuran besar. Besar reduksi dosis efektif total dari penggunaan pelindung tiroid pada FOV berukuran besar (20x19 cm) adalah 18,0% (dari 254,3 µSv menjadi 208,5 µSv), pada FOV berukuran sedang (16x10 cm) adalah 40,1% (dari 249,0 µSv menjadi 149,1 µSv), dan pada FOV berukuran kecil (16x7 cm) adalah 38,7% (dari 180,3 µSv menjadi 110,5 µSv).…”
Section: Fungsi Pelindung Tiroid Pada Teknik Radiografi Sefalometri Dunclassified
“…Lens ve tiroid radyasyon dozları yapılan diğer çalışmalarla da uyumludur. 29,30 Bu çalışma ile BT çekimlerinde lens, oral mukoza ve tiroidin önemli oranda radyasyona maruz kaldığı belirlenmiştir. Tekrar çekimlerinde endikasyonu kesin olmayan veya tarama amaçlı çekimlerde organ dozlarının dikkate alınması gerekliliği bu çalışma ile ortaya konulmuştur.…”
Section: Introductionunclassified
“…Thus, to move towards preserving general health, using bismuth shields is a reccommended assay for reducing radiation doses in female breast during MDCT examinations (11)(12)(13)(14)(15). For the first time, Hopper et al (16) reported that bismuth shields can decrease the average radiation dose by 57%.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the breast shield provided a 37.12% decrease in radiation dose. Thus, studies point to decreases in radiation levels in the breast tissue by approximately 50% using bismuth shields, but due to the absence or unavailability of these shields in all parts of the world, plus some concerns about bismuth shields increasing radiation dose through scatter (15) and lack of data or consensus about their impact on image quality, this technique is currently not being widely used. Studies have reported on the effects of breast bismuth shields on image quality during chest and lung CT exams, but there is little information to use in coronary CTA.…”
Section: Introductionmentioning
confidence: 99%